Utilização de escória produzida em alto-forno a carvão vegetal como agregado graúdo e miúdo para concreto - ALMEIDA, Gyselle Maciel de (Universidade Federal do Pará, 2017)
The steel production requires many stages and generates large quantities of slag, these rising stocks are worrying metallurgists and environmentalists aiming the rational use of this industrial byproduct, in order to minimize possibles environmental problems. In this sense, the civil construction presents a quite fit sector to the use of reuse techniques, of wastes and byproducts, from different industries. Besides the environmental benefits, like the reduction of non-renewable natural resources, the emergence alternative construction materials enables the reduction in the cost of construction, important factor when is evaluated the deficiency existing housing in Brazil. In this research is studied a possible recycling of blast furnace slag, from of hypothesis that is viable its utilization as coarse aggregate and fine aggregate for concretes. Its influence is studied on the characteristic of concrete in fresh state (workability) and in hardened state (axial compressive strength, tensile strength by diametral compression and elastic modulus). In this work the content of substitutions of blast furnace slag was diversified, the water-to-cement ratio and the ages of breaking of the specimens. The used methodology was based on lab rehearsals and in the use of statistical tools to validate the results. With the results obtained in this study, it was found that the use of large amounts of blast furnace slag as coarse and kid aggregate for concrete, in general, had no influence or not exerted a positive influence in the studied properties. We conclude that the findings pointed to the non-technical viability of using this waste as aggregates for concrete.